2015
DOI: 10.4238/2015.march.27.2
|View full text |Cite
|
Sign up to set email alerts
|

Increased human epididymis protein 4 in benign gynecological diseases complicated with chronic renal insufficiency patients

Abstract: ABSTRACT. We examined the serum concentration of human epididymis protein (HE4) in patients with benign gynecological diseases complicated with chronic renal deficiency and its significance in the differential diagnosis of benign and malignant gynecological diseases. Serum HE4 and cancer antigen 125 concentrations were detected by chemiluminescence. Clinically or pathologically confirmed gynecological diseases were grouped and retrospectively analyzed, including 50 cases of gynecological benign diseases, 35 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…The results indicated that the S-HE4 level in the OC and CKD groups was significantly higher than that in the HC group (P<0.001), and that no significant difference regarding S-HE4 levels was identified between the OC and CKD groups. These observations were consistent with those of the study by Lv et al (17), which demonstrated that S-HE4 levels in OC and CKD patients significantly increased in comparison to the levels detected in the HC group, and the study indicated that the S-HE4 level in the CKD group was higher than that in the OC group. The present study and that of Lv et al (17) indicate that the diagnosis of OC on the basis of S-HE4 levels may be problematic in patients who suffer from CKD.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The results indicated that the S-HE4 level in the OC and CKD groups was significantly higher than that in the HC group (P<0.001), and that no significant difference regarding S-HE4 levels was identified between the OC and CKD groups. These observations were consistent with those of the study by Lv et al (17), which demonstrated that S-HE4 levels in OC and CKD patients significantly increased in comparison to the levels detected in the HC group, and the study indicated that the S-HE4 level in the CKD group was higher than that in the OC group. The present study and that of Lv et al (17) indicate that the diagnosis of OC on the basis of S-HE4 levels may be problematic in patients who suffer from CKD.…”
Section: Discussionsupporting
confidence: 83%
“…Recent studies reported that serum HE4 concentrations significantly increase in patients with chronic kidney disease (CKD), renal failure and heart failure (14)(15)(16). In the study by Nagy et al (14), increased HE4 levels were measured in patients with early stage CKD, indicating that the serum HE4 level is significantly affected by the estimated glomerular (17) demonstrated that patients with chronic renal deficiency exhibited elevated serum HE4 levels that were significantly higher than those of patients with benign gynecological diseases. These data indicate that serum HE4 concentrations may be affected by variable demographical factors or by non-malignant diseases.…”
Section: Introductionmentioning
confidence: 98%
“…In a study of Lv et al a higher level of HE4 was observed in patients with chronic renal disease as compared to OC and EC, although the difference was not statistically significant. In their study, no statistically significant differences in CA125 serum levels between patients with chronic renal disease and controls were observed [21].…”
Section: Discussionmentioning
confidence: 99%
“…The direct expression and the consequent release of HE4 in the bloodstream from the impaired kidney might further complicate the situation, even if this additional potential source of HE4 has not been carefully studied. Some authors have reported an increase of serum HE4 concentrations in patients with any grade of kidney injury, and a consistent HE4 expression has been observed in kidneys within the distal convoluted tubules [12][13][14][15]. Thus, HE4 may unpredictably increase in serum because of a raised kidney expression and an impaired renal elimination and these amounts may cumulate in the bloodstream with those of ovarian origin.…”
Section: Discussionmentioning
confidence: 95%
“…As reported for other tumour markers, the adjustment of HE4 concentrations by formulas or algorithms might be a viable option if the impaired renal function is the only non-tumour mechanism increasing the marker values in serum by limiting its clearance from the circulation [6,11]. However, Galgano et al [12] characterized a considerable expression of the gene encoding for HE4 in renal tissue and more recent studies have shown an increase of HE4 expression and/ or its serum concentrations in patients with any grade of kidney injury [13][14][15]. Additional studies have reported HE4 is upregulated in fibrotic kidneys, suggesting it as a potential biomarker of renal fibrosis and as a therapeutic target [16,17].…”
Section: Introductionmentioning
confidence: 99%